(untitled) (International Journal of Built Environment and Sustainability, 2025)
The process of urbanization in developing countries is characterized by a double-edged sword, especially with regard to indigenous communities. This research aims to analyze how has urbanization and the socio-economic effects on the traditional settlement patterns and Malay community in the village of Kampung Sayong, Kuala Kangsar, Perak, Malaysia, over the period between 1900 and 2022. This research employs both qualitative and quantitative data analysis techniques, such as questionnaires, interviews, observation, and data from tools such as SPSS V11, Google Earth mapping, and drone technology. The findings reveal a nuanced picture: the process has provided much-needed advances in physical development, employment prospects, and network access. It has caused the decline of conventional farming practices and the breakdown of social relations, which has characterized the village. The findings of this study underscore the importance of urban planning approaches that will preserve claims to tangible and intangible cultural assets, as well as issues related to land tenure, lack of adequate housing, and environmental conservation. Thus, this paper has benefited the global discussion on sustainable urbanization. It provides information from the Kampung Sayong Kuala Kangsar Perak with lessons that policymakers would require to attain sustainable modernization while protecting the Malay local cultures.